Black Monday : [compact disc, unabridged] : a novel - Reiss, Bob (Blackstone Audio, 2007)
When a Muslim cleric predicts planes will fall from the sky, America braces for a terrorist attack. But when the prediction proves true, the real cause is far more terrifying: a microbe that eats oil, effectively destroying all gas-operated mechanisms.